The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/mrd.90001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation of tetraploid rat blastocysts after fusion of two‐cell embryos

Abstract: Gene targeting technology is not available in the rat which is an animal model of major importance, e.g., in cardiovascular research. This is due to the fact that the rat embryonic stem cell (ESC)-like cells established by several groups do not form germ-line chimeras when injected into blastocysts. In the mouse, the aggregation of ESC with tetraploid embryos has allowed the generation of animals completely derived from these cells. However, aggregation of rat ESC-like cells with tetraploid rat embryos has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Based on comparisons with controls, and the observation that diploid cells tend to display a strong competitive advantage in 4n:2n chimeras (see below), the conclusions are likely to be valid. While electrofused blastomeres of the rat and pig are were reported to develop as homogeneously tetraploid embryos (Prather et al, 1996;Krivokharchenko et al, 2002), rabbit and bovine embryo electrofused at the two-cell stage displayed occasional (rabbit) and frequent (cow) mosaic (4n:2n) preimplantation development for unknown reasons (Ozil and Modlinski, 1986;Iwasaki et al, 1989;Curnow et al, 2000). In light of this, it may be prudent to consider the possibility that other strains of mice may not behave as those detailed above (Table 1).…”
Section: Blastomere Fusionmentioning
confidence: 99%
“…Based on comparisons with controls, and the observation that diploid cells tend to display a strong competitive advantage in 4n:2n chimeras (see below), the conclusions are likely to be valid. While electrofused blastomeres of the rat and pig are were reported to develop as homogeneously tetraploid embryos (Prather et al, 1996;Krivokharchenko et al, 2002), rabbit and bovine embryo electrofused at the two-cell stage displayed occasional (rabbit) and frequent (cow) mosaic (4n:2n) preimplantation development for unknown reasons (Ozil and Modlinski, 1986;Iwasaki et al, 1989;Curnow et al, 2000). In light of this, it may be prudent to consider the possibility that other strains of mice may not behave as those detailed above (Table 1).…”
Section: Blastomere Fusionmentioning
confidence: 99%
“…Krivokharchenko et al (2002) observed 96% fusion rate after electrofusion of 2-cell stage embryos in rat when used 0.6 kV/cm DC pulses for 20 μs duration.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 89%
“…Fusion of embryos induced by electrical pulses was used for production of tetraploid embryos in different species including mouse (Sekirina et al, 1997), rabbit (Ozil and Modlinski, 1986), pig (He et al, 2013), bovine (Darabi et al, 2008) and rat (Krivokharchenko et al, 2002).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to produce parthenogenetic tetraploid embryos by inhibiting the formation of both first (1 st PB) and second polar bodies (2 nd PB) with cytochalasin B or other cytokinesis-inhibition drugs during parthenogenetic activation of oocytes [16,17]. The third method is to fuse two diploid blastomeres at the 2-cell stage embryo with either polyethylene glycol (PEG) [18,19], inactivated Sendai virus [20] or by electrofusion. Among these fusion methods, electrofusion is the most widely used tool for the production of tetraploid embryos [1,21,22] as it is safer than the chemical-or virus-mediated methods and more convenient and economical than microsurgical injection [14].…”
Section: Introductionmentioning
confidence: 99%